Isolation and characterization of acetic acid bacteria from pineapple peel fermentation (Ananas comosus) - NATALIA SRI MARTANI; HANASIA HANASIA; OKTAVIANI NAULITA TURNIP; HANDAYANI HALIK; I GDE HARY EKA ADNYANA (Society for Indonesian Biodiversity, 2025)
Abstract. Martani NS, Hanasia, Turnip ON, Halik H, Adnyana IGHE. 2025. Isolation and characterization of acetic acid bacteria from pineapple peel fermentation (Ananas comosus). Biodiversitas 26: 789-798. Pineapple (Ananas comosus) is rich in bioactive compounds and is often considered waste, especially its peel. The fermentation of pineapple peel can yield value-added goods, including probiotic drinks that promote digestive health. Acetic Acid Bacteria (AAB) are significant microorganisms in fermentation, converting ethanol into acetic acid, hence offering preservation advantages and probiotic qualities. This study aimed to isolate and characterize acetic acid bacteria from the fermentation of pineapple peel and evaluate its antibacterial properties. The fermentation occurred spontaneously without the use of a starting culture, utilizing three distinct formulas. On the third day of fermentation, the fermented liquid was extracted and characterized by 16S rRNA gene sequencing. The findings indicated that the identified AAB was Acetobacter fabarum strain 2567, exhibiting 97% homology. The antibacterial activity of A. fabarum filtrate at concentrations of 5-75% was tested against the pathogens Escherichia coli and Shigella dysenteriae using the disk diffusion method; however, no antibacterial activity was observed against either pathogen. The study underscores the need for further research to evaluate the antibacterial potential of A. fabarum against other pathogens using methods such as micro-dilution or well diffusion, highlighting the urgency of this line of investigation.